Resilience in infertile couples acts as a protective factor against infertility-specific distress and impaired quality of life - Herrmann, Darja; Scherg, Horst; Verres, Rolf; Hagens, Cornelia von; Strowitzki, Thomas; Wischmann, Tewes (Journal of assisted reproduction and genetics, 2011)
Our hypothesis was that resilience (=psychosocial stress-resistance) reduces infertility-specific distress and maintains quality of life of infertile couples.
Gesehen am 05.10.2022